Assessment of the frequency and association with morbidity of DNA markers in multinational administrative divisions based on indigenous population data (based on cardiovascular diseases) - E. V. Balanovskaya; A. Yu. Potanina; S. M. Koshel; D. S. Adamov; I. V. Evsyukov; A. L. Borisova; M. S. Pokrovskaya; A. N. Meshkov (Кардиоваскулярная терапия и профилактика)
Information on morbidity is presented in statistical reports for the entire population of multinational subjects of Russia, but population Biobanks contain information on individual peoples.Aim. To develop a technology for assessing the frequency of deoxyribonucleic acid (DNA) markers for administrative units based on indigenous population data, which will make it possible to assess the relationship between the frequency of DNA markers and morbidity.Material and methods. The Biobank of Northern Eurasia presented the frequencies of 24 DNA markers associated with cardiovascular disease (CVD) for 86 indigenous peoples of Russia (6227 DNA samples). Information on the ethnic composition of 83 Russian regions was extracted from the 2010 census, and the CVD incidence in 85 Russian regions (2020-2021) was assessed by data from the Ministry of Health of Russia.Results. The data on the gene pools of the indigenous population and the ethnic composition of Russian regions made it possible to assess the frequencies of 24 DNA markers in 85 Russian regions. The obtained frequencies allowed us to directly assess their relationship with CVD in Russia — chronic rheumatic heart diseases, cardiomyopathy, coronary artery disease, hypertension, acute myocarditis. Technology application data are presented in the form of tables and genogeographic maps of the distribution of 24 CVD DNA markers in Russian subjects, the geography of morbidity in Russian subjects for five CVDs, and the correlation of the distribution of the frequency of CVD DNA markers and the incidence of CVD among the population of Russia.Conclusion. The proposed technology for assessing the modern gene pool in Russian subjects based on the data on the gene pool of the indigenous peoples of Russia for the first time made it possible to assess the relationship between clinically significant DNA markers and morbidity in Russia.